AMANAT DALAM SAMPIRAN PANTUN MELAYU KENEGERIAN KOTORAJO RANTAU KUANTAN - Mayasari, Sri Ayu; Rahman, Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This Research study about commendation which is there are in addition of poetry of Malay of country Kotorajo. This Research aim to for mendeskripsikan of commendation in addition of poetry of Malay of country Kotorajo. Source of Data in this research is narasumber representing society in countryside of Kotorajo of subdistrict of Pestle Go downstream to Defect. Narasumber is one who understand poetry and know its background and also remain to or come from countryside Kotorajo. Method used in this research is descriptive analyse. Technique of data collecting in this research use technique ( 1) observation, that is to obtain;get data and information of about poetry utilized by society Kotorajo. This Information got from narasumber that is all prominent society knowing about poetry. ( 2) interview, that is to utilize truth and to look for more valid data. Interview used with two way of that is with direct record-keeping and the record. And ( 3) record, that is used to get data of poetry directly from narasumber. Technique analyse data used in mengalisis of result of this research is technique of study of book of data obtained by writer of through read and involve each;every addition couplet. Commendation which is there are in the poetry more dominant about exploiting natural product, tradition or culture, and also about values of history of exist in Country Kotorajo.Keywords: Commendation, addition, poetry.